Xenophon's Socratic education : reason, religion, and the limits of politics - Sebell, Dustin (University of Pennsylvania Press, 2021)
"This is the sequel to the author's first book, The Socratic Turn. He suggests that perhaps there is no better place to start looking into the possibility that Socrates was teaching others something about morality or politics-or trying and failing to do so-in hopes of learning something from them about religion, than the fourth and final book of Xenophon's Memorabilia. Alfarabi, the Islamic philosopher of the Middle Ages, wrote a book titled The Philosophy of Plato, Its Parts, the Rank of Order of Its Parts, from Beginning to End, and Leo Strauss once said, with that in mind, that Book IV of Xenophon's Memorabilia presents "the core of Socrates' teaching according to its intrinsic order from its beginning to its end." Sebell writes that, we have, in Book IV, the whole course of a Socratic education, touching on everything relevant to the purpose, in order, from start to finish. And this book is devoted, therefore, to Book IV of his Memorabilia"--